Multi-electrolyte disturbance and supplementation in severely malnourished hospitalized adolescents with restrictive eating disorders - Eva-Molly Petitto Dunbar; Chase Pribble; Jennifer Cueto; Andrea B. Goldschmidt; Christina Tortolani; Abigail A. Donaldson (Journal of Eating Disorders, 2023)
Abstract Background This study describes the prevalence of hypophosphatemia, hypokalemia, and/or hypomagnesemia and resulting electrolyte supplementation during refeeding in severely malnourished youths hospitalized for restrictive eating disorders. Methods Hospitalized patients between 11-26y (N = 81) at < 75% treatment goal weight (TGW) were assessed through retrospective chart review. Outcomes were compared between participants < 70% TGW and those 70–75% TGW. Nutritional rehabilitation started at 1750 kcals/day and advanced by 500 kcal every other day until target intake was achieved. Associations between %TGW on admission; hypophosphatemia, hypokalemia, and/or hypomagnesemia; and electrolyte supplementation were examined. Results Of the 24 (29.6%) participants with hypophosphatemia, hypokalemia, and/or hypomagnesemia, 7 (8.6%) received supplementation; the remainder corrected without supplementation. Participants < 70% TGW did not differ from those 70–75% TGW on rates of these conditions or need for supplementation. Conclusions Hospital-based nutritional rehabilitation did not confer increased rates of hypophosphatemia, hypokalemia, and/or hypomagnesemia or need for electrolyte supplementation in patients < 70% TGW compared to those 70–75% TGW. While additional research is needed to establish clinical practice guidelines on electrolyte management in this population, our findings suggest that nutritional rehabilitation may be reasonably undertaken without prophylactic electrolyte supplementation, even in patients < 70% TGW.